The determinants of goal realization and the significant role of self-efficacy in the Malaysian franchise industry - Nik Mat, Nik Kamariah (The Academy of Business and Retail Management (ABRM), 2018)
The franchising industry in Malaysia is worth more than RM27 billion in 2017 and is rising. However, the local franchisees are still lagging behind their international players in their home country. Hence, the objective of this study is to determine the factors that lead to the innovative goal realization of the local food franchisees. This study utilizes quantitative research design by distributing 400 questionnaires consisting of measurement for seven latent variables.The instruments consist of 45 items adapted to suit the local franchise industry using a 7-point Likert scale. A response rate of 42% (169) was obtained and the data were analyzed using structural equation modeling (SEM) in AMOS. The path model demonstrates that nine relationships are significant out of twelve hypotheses examined. It signifies that to achieve goal realization, a franchisee needs to undergo a process. It started from goal desire and ends with goal realization. Self-efficacy and goal desire significantly affect goal intention which subsequently effect implementation desire. Next, implementation desire influence implementation intention and self-efficacy. Subsequently, implementation intention and self-efficacy influence plan enactment. Finally, implementation desire and plan enactment are the two significant factors influencing innovative goal realization.